Pengaruh Fase Apill Pada Simpang Terhadap Perilaku Menunggu Pengguna Sepeda Motor Di Kota Tegal - Dwiyantara, Arga; Pramudyawardani , Heni Putri; Kamal , Muhammad Rikzam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2018)
Intersection is a critical area on a highway where a point of conflict and where bottlenecks due tothe merging of two or more roads. The junction arrangements that do not fit will cause trafficproblems, particularly the intersection you have installed APILL. Violations often occur are agresivedriving behavior in the form of the behavior of the wait. Based on existing conditions, the behaviorof waiting that occurred at an intersection with two and four phase settings have a difference.Violations committed by users i.e. a motorcycle broke through APILL, stop at the stop line and theopposing lanes consuming. APILL phase setting should resolve the problems of the particularbehavior of the wait. Methods of analysis used i.e. the dependent samples T-test test with SPSS16.0 program use. Based on the current test sig (2-tailed) of > 0.05 0.628 then it can be concludedthat there was no significant difference between the behavior of waiting at an intersection that has asetting of two and four phases.